Serum immunoglobulin levels in children with acute bacterialmeningitis - M, Khalaf, Mus’ab (Tikrit Journal of Pharmaceutical Sciences, 2023)
To assess serum level of immunoglobulins (IgG, IgA, IgM) in children with acute bacterial meningitis before therapy and at the end of intensive antibiotic therapy and in COMparison 1 heallity age aiid scx mittchicd vonirsls. Out of 37 vases adinived ta Thi-Als Atheer pediatric hospital (Mosul city) between January 2005 and July 2007, 29 cases proved to be a case of Haemophilus influenzae meningitis. Two died during the follow up period and 27 completed the study. Also included 30 apparently healthy age and sex matched subjects taken as control group. Initially from both group (patients and control) Sml venous blood samples were taken and assay of serum immunoglobulin (IgG, IgA, IgM) were done by single radial immunodiffusion method using commercial kits. After two weeks of intensive antibiotic therapy another blood samples were taken from the patients and assay of serum immunoglobulin levels were done using the same method and the same commercial kits. Initially before therapy there was a significant reduction in all immunoglobulin levels (IgG, IgA, IgM) in children with acute bacterial meningitis in comparison to controls. After 2 weeks of intensive antibiotic therapy, there was no significant difference in the mean serum immunoglobulin levels between the patients and controls. Acute bacterial meningitis as a disease and the intensive antibiotic therapy do affect the humoral immune response as reflected by the serum immunoglobulin levels (IgG, IgA, IgM).